IMPACT OF THE GROWTH ENHANCEMENT SUPPORT SCHEME (GESS) ON MAIZE FARMERS IN DUTSINMA LOCAL GOVERNMENT AREA OF KATSINA STATE, NIGERIA - Ibrahim, H. Y.; Ale-ojo, H. A.; Wahab, M. J. (FUDMA Journal of Sciences, 2023)
The study examined the impact of the Growth Enhancement Support Scheme (GESS) on maize farmers in Dutsin ma, Katsina state, Nigeria. Simple Random sampling was used to select 100 beneficiaries while purposive sampling was used to select100 non-beneficiaries of the scheme. Data were analyzed using descriptive and inferential statistics as well the Propensity Score Matching technique. The likelihood that a household selected at random will participate in the scheme was 66.7%. The likelihood of participation in the GESS increases with household size (p<0.05), educational level (p<0.10), association member (p<0.01) and extension contact (p<0.10), while, the number of maize plots (p<0.05) and dependency ratio (p<0.05) reduces the likelihood of participating in the GESS. The Average Treatment Effect on the treated (ATT) for TFP shows that Maize productivity for the beneficiaries of the scheme increased by a factor of 2.25. The Average Treatment Effect on (ATE) shows that the scheme increased maize productivity by a factor of 0.855, while the Average Treatment Effect on the untreated (ATU) shows that maize productivity for the non-beneficiaries could have increased by a factor of 0.73 if they had benefited from the scheme. The Average Treatment Effect on the treated (ATT) for Gross Margin shows that maize income for the beneficiaries of the scheme increased by N58614 per hectare of area cropped with Maize. On the other hand, the Average Effect of the Treatment (ATE) shows that the scheme increased maize income by N15854, while the average treatment on the untreated ATU shows that maize income